Arginine deficiency leads to impaired cofilin dephosphorylation in activated human T lymphocytes - Feldmeyer, Nadja; Wabnitz, Guido H.; Leicht, Stefan; Luckner-Minden, Claudia; Schiller, Martin; Franz, Thomas; Conradi, Roland; Kropf, Pascale; Müller, Ingrid; Ho, Anthony Dick; Samstag, Yvonne; Munder, Markus (International immunology, 2012)
The amino acid arginine is fundamentally involved in the regulation of the immune response during infection, inflammatory diseases and tumor growth. Arginine deficiency (e.g. due to the myeloid cell enzyme arginase) inhibits proliferation and effector functions of activated T lymphocytes. Here, we studied intracellular mechanisms mediating this suppression of human T lymphocytes. Our proteomic analysis revealed an impaired dephosphorylation of the actin-binding protein cofilin upon T-cell activation in the absence of arginine. We show that this correlates with alteration of actin polymerization and impaired accumulation of CD2 and CD3 in the evolving immunological synapse in T cell-antigen presenting cells conjugates. In contrast, T-cell cytokine synthesis is differentially regulated in human T lymphocytes in the absence of arginine. While the production of certain cytokines (e.g. IFN-γ) is severely reduced, T lymphocytes produce other cytokines (e.g. IL-2) independent of extracellular arginine. MEK and PI3K activity are reciprocally regulated in association with impaired cofilin dephosphorylation. Finally, we show that impaired cofilin dephosphorylation is also detectable in human T cells activated in a granulocyte-dominated purulent micromilieu due to arginase-mediated arginine depletion. Our novel results identify cofilin as a potential regulator of human T-cell activation under conditions of inflammatory arginine deficiency.
Gesehen am 25.06.2021